Clinical Isolates of Non-O157 Shiga Toxin-Producing Escherichia coli: Serotypes, Virulence Characteristics, and Molecular Profiles of Strains of the Same Serotype - Eklund, Marjut (American Society for Microbiology, 2001)
All human Shiga toxin-producing Escherichia coli (STEC) non-O157 strains (n = 56) isolated in Finland from 1990 to August 2000 were characterized for the O:H serotype, stx(1) and stx(2) genes, production of enterohemolysin, and sensitivity to 12 antimicrobial agents. Strains of the same serotype were genotyped by pulsed-field gel electrophoresis (PFGE) after XbaI restriction of total DNA. The 56 non-O157 isolates belonged to 29 serotypes. Two of the serotypes (O102:H7 and OX181:H49) have not previously been described as being associated with STEC infections in humans or isolated from animals. Thirty-four strains (61%) within seven serotypes (O103:H2 [14 isolates], O26:H11 [6 isolates], O145:H28 [4 isolates], O145:HNM [3 isolates], O15:HNM [3 isolates], OX174:H21 [2 isolates], and O Rough:HNM [2 isolates]) were represented by more than one isolate. Of these strains, O103:H2 isolates were divided into seven, O26:H11 isolates were divided into four, and the rest within a serotype were divided into two genotypes in PFGE. In PCR, 31 (55%) of the 56 strains were positive for the stx(2) gene only and 24 strains (43%) were positive for stx(1) only. One strain (O43:H2) carried both stx(1) and stx(2). Forty-two strains (75%) produced enterohemolysin, and 39 strains (70%) possessed the eae gene. Of the latter 39 strains, 36 (92%) were enterohemolytic, whereas only 6 (35%) of the 17 isolates lacking the eae gene were enterohemolytic (P < 0.001). The majority of the strains (44 strains, 79%) were sensitive to all 12 antimicrobials tested. Of the 56 strains, 20 (36%) were associated with small family outbreaks in nine families and 14 (25%) were associated with recent travel abroad.